Lipidome changes in alcohol‐related brain damage. Issue 2 (11th November 2021) - Smith, Caine C.; Sheedy, Donna L.; McEwen, Holly P.; Don, Anthony S.; Kril, Jillian J.; Sutherland, Greg T.
Abstract: Alcohol‐related brain injury is characterized by cognitive deficits and brain atrophy with the prefrontal cortex particularly susceptible. White matter in the human brain is lipid rich and a major target of damage from chronic alcohol abuse; yet, there is sparse information on how these lipids are affected. Here, we used untargeted lipidomics as a discovery tool to describe these changes in the prefrontal, middle temporal, and visual cortices of human subjects with alcohol use disorder and controls. Significant changes to the lipidome, predominantly in the prefrontal and visual cortices, and differences between the white and grey matter of each brain region were identified. These effects include broad decreases to phospholipids and ceramide, decreased polyunsaturated fatty acids, decreased sphingadiene backbones, and selective decreases in cholesteryl ester fatty acid chains. Our findings show that chronic alcohol abuse results in selective changes to the neurolipidome, which likely reflects both the directs effects on the brain and concurrent effects on the liver. Abstract : Alcohol‐related brain damage is characterized by widespread white matter atrophy. In this study, we profiled the lipidome of three post‐mortem brain regions from people with chronic alcoholism and controls. Chronic alcoholism resulted in a general decrease in both the chain length and the level of unsaturation of fatty acids and specific decreases in both glycerophospholipids and ceramides. Interestingly, we also observed these changes in the primary visual cortex despite an absence of gross pathological changes. These lipid anomalies likely arise from both the directs effects on the brain and concurrent effects on the liver.